PSYCHOLOGICAL COUNSELING AND PSYCHOTHERAPY IN CLINICAL MEDICAL PRACTICE – BIOPSYCHOSOCIONOETHICAL ASPECTS - Zarlevski, Kiril (E-Journal VFU, 2026)
The article analyzes the specific features of psychological counseling and psychotherapy in clinical medical practice through the prism of the integrative biopsychosocionoethical model. Some of the more significant aspects of the application of a non-medical model of working with patients in a medical (hospital) environment are examined. Emphasis is placed on the psychology of the patient, illness, and the process of being ill, and their significance for the process of counseling and therapy. Particularly important for analysis are the functions, tasks, and goals of the psychologist and psychotherapist in hospital institutions. Last but not least, various techniques and problems of psychological counseling in a hospital environment are considered, as well as the applied aspects of medical psychotherapy.